The German Bildungsroman from Wieland to Hesse - Swales, Martin (Princeton essays in literature., 1978)
Although some of the most distinguished German novels written since about 1770 are generally considered to be Bildungsromane, the term Bildungsroman is all too frequently used in English without an awareness of the tradition from which it arose. Professor Swales concentrates on the roles of plot, characterization, and narrative commentary in novels by Wieland, Goethe, Stifter, Keller, Mann, and Hesse. By pointing out that the goal in each work is both elusive and problematic, he suggests a previously unsuspected ironic intent. His analysis adds to our awareness of the potentialities inheren.